Consuming symbolism: marketing D-Day and Normandy. Issue 2 (15th March 2017) - MacCarthy, Martin
ABSTRACT: This exploratory study examines experience engineering at select tourist sites of the D-Day landing area in Normandy, France. Using Holt's 1995 typology of symbolic consumption as an interpretive frame, a number of significant museums, cemeteries, gun batteries, beaches and plinths were examined. Interactions with the public at these sites including the introspection of five academics were compiled, compared and interpreted. The experiences of D-Day visitors were then considered in relation to the range of consumption metaphors afforded by Holt's model. The results are consistent with Holt's explanation of symbolic consumption. These rich and nuanced examples of experiential consumption are typified by the four consumption metaphors of Holt's model; namely, Experience, Integration, Play and Classification. By doing this the widespread practise, scale and techniques of experience engineering by site managers/curators is evident. The differing and inconsistent staged authenticity by stakeholders and curators invites implicational consideration.